Induction of Protective Immunity against Murine Gammaherpesvirus 68 Infection in the Absence of Viral Latency - Jia, Qingmei (American Society for Microbiology (ASM), 2010)
Human gammaherpesviruses, Epstein-Barr virus, and human herpesvirus 8/Kaposi's sarcoma-associated herpesvirus are important pathogens associated with diseases, including lymphomas and other malignancies. Murine gammaherpesvirus 68 (MHV-68) is used as an experimental model system to study the host immune control of infection and explore novel vaccine strategies based on latency-deficient live viruses. We studied the properties and the potential of a recombinant MHV-68 (AC-RTA) in which the genes required for persistent infection were replaced by a constitutively expressed viral transcription activator, RTA, which dictates the virus to lytic replication. After intranasal infection of mice, replication of AC-RTA in the lung was attenuated, and no AC-RTA virus or viral DNA was detected in the isolated splenocytes, indicating a lack of latency in the spleen. Infection of the AC-RTA virus elicited both cellular immune responses and virus-specific IgG at a level comparable to that elicited by infection of the wild-type virus. Importantly, vaccination of AC-RTA was able to protect mice against subsequent challenge by the wild-type MHV-68. AC-RTA provides a vaccine strategy for preventing infection of human gammaherpesviruses. Furthermore, our results suggest that immunity to the major latent antigens is not required for protection.